Organization and structure of the mouse interleukin-2 gene. - Fuse, A (1984)
We have cloned a chromosomal DNA segment which covers the entire sequence for the murine interleukin-2 gene and analysed the structure of the gene. The coding regions are separated into four blocks by three introns each of which is located similarly to the corresponding human gene. The exon sequences can be aligned perfectly with the previously cloned cDNA sequence. Of particular interests is the presence of sequences within the 5'-flanking region which are highly conserved between mouse and man. The conserved region which spans more than 400 base pairs may play a role in the regulation of IL-2 gene expression.